(untitled) (Palestine Technical College Journal for Research and Studies, 2023)
The current study aimed to investigate the effectiveness of the play strategy in helping third grade students acquire concepts of national and life education in Palestine and to identify their attitudes toward it. To achieve the objectives of the study, the researcher employed both the descriptive and quasi-experimental approaches. Two instruments were designed for the study: a concepts test and an attitude scale. The study was conducted on one group consisting of (16) male and female third grade students during the first semester of the 2022–2023 academic year. After conducting the experiment, the results revealed statistically significant differences at the significance level (α ≤ 0.05) between the mean scores of the experimental group in the concepts test due to the pre- and post-application, in favor of the post-application. The findings also showed that students’ attitudes toward the play strategy after its use in teaching national and life education exceeded the minimum acceptable level of 70%. In addition, the strategy demonstrated a high degree of effectiveness in developing students’ acquisition of national and life education concepts, scoring (1.66) according to Black’s modified gain ratio. Finally, the study presented several recommendations, the most important of which were raising the awareness of school administrations, teachers, and parents about the importance of making children’s teaching and learning as child-centered as possible, and emphasizing the value of play as a teaching strategy due to its role in supporting children’s academic progress. The study also highlighted the importance of providing teachers with the equipment and tools necessary to effectively employ play in teaching. Furthermore, teachers should be encouraged to use play creatively and actively, as it contributes to simplifying instruction, reviewing and summarizing concepts, and attracting children’s attention.